Training needs of the Andalusian teachers on the educational attention to the students with high intellectual capacities - Corujo Vélez, Mª del Carmen; Alicia, Gómez Rodríguez; Hervás Gómez, Carlos (IJERI: International Journal of Educational Research and Innovation, 2018)
The present work aims to know the knowledge of the teachers of Primary, Secondary and Secondary Education of different provinces of Andalusia (Spain) on the students with specific educational support needs, specifically on the ones called in the category "students with high intellectual capacities" as established in the Instructions of March 8, 2017 of the General Directorate of Participation and Equity, which updates the Protocol of Detection, Identification of Students with Specific Needs of Educational Support and Organization of the educational response of the Ministry of Education of the Regional Government of Andalusia. For this purpose, a self-administered questionnaire of 20 questions, with a Likert type scale, is prepared, with a total of 72 teachers. The results obtained, although they are not very representative, show an evident formative need in the areas related to the identification, didactic and intervention strategies with this students, as well as ignorance about resources and specific materials to facilitate their educational inclusion in the classroom and to prevent the school failure.